2018
DOI: 10.3390/atmos9050159
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cold Fronts on Variability of Daily Surface O3 over the Houston-Galveston-Brazoria Area in Texas USA during 2003–2016

Abstract: Abstract:We investigated the impacts of cold fronts on area-wide peak O 3 and regional background O 3 mixing ratios on a daily scale over the Houston-Galveston-Brazoria (HGB) area of southeastern Texas during the O 3 seasons (April-October) of [2003][2004][2005][2006][2007][2008][2009][2010][2011][2012][2013][2014][2015][2016]. Back trajectories showed that an 18h time lag existed between arrival of cold fronts in the HGB area and onset of a predominately northerly flow. Cold fronts showed increasing effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The high O 3 days (May 13 and 14) had transport of continental airmass from the North. Previous studies have shown that long-range transport of the northern continental air mass contributes to an elevated regional O 3 background in Texas (Lei et al, 2019(Lei et al, , 2018. May 24 and 25 also had continental airmass from the North but these days did not have the high actinic flux required for the peak O 3 production (Fig.…”
Section: Case Study: May 13-14 High Ozone Episodementioning
confidence: 86%
“…The high O 3 days (May 13 and 14) had transport of continental airmass from the North. Previous studies have shown that long-range transport of the northern continental air mass contributes to an elevated regional O 3 background in Texas (Lei et al, 2019(Lei et al, , 2018. May 24 and 25 also had continental airmass from the North but these days did not have the high actinic flux required for the peak O 3 production (Fig.…”
Section: Case Study: May 13-14 High Ozone Episodementioning
confidence: 86%
“…MDA8 ozone level is in the middle for Oscillation and Northerly Cluster with the mean values of 37.60 ppbv and 35.40 ppbv in HGB and of 42.93 ppbv and 41.01 ppbv in SA, respectively. Both Northerly and Oscillation Cluster bring polluted continental air masses to the region which can elevate background ozone (Lei et al, 2018; Rappenglück et al, 2008). Oscillation Cluster has slightly higher ozone concentrations than Northerly Cluster because the higher temperature in Oscillation Cluster can result in more production of ozone.…”
Section: Ozone Concentrations and Spatial Distributionsmentioning
confidence: 99%
“…In summer, westward extension of the Bermuda subtropical high favors the development of a southerly low‐level jet over the Southern Great Plains, while transient processes (e.g., passages of frontal systems) may disturb such flow patterns at times (Klein et al, ; Lei et al, ; Zhu & Liang, ). During summer months, O 3 over the Southern Great Plains shows correlation with the Bermuda High variations: a stronger/weaker Bermuda High leads to lower/higher summer mean O 3 in the region with a magnitude of variation of around 6 ppbv (Zhu & Liang, ).…”
Section: Introductionmentioning
confidence: 99%